2019
DOI: 10.2334/josnusd.18-0380
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative changes in oral bacteria number in patients undergoing cardiac valve surgery

Abstract: Perioperative oral care can reduce the risk of postoperative infections. This study examined 1) changes in oral bacteria counts during the perioperative period and 2) differences in bacteria counts in patients with or without endotracheal intubation. 47 patients who visited our hospital dental clinic prior to cardiac valve surgery were prospectively recruited. The number of bacteria on the tongue, tooth surface, and buccal vestibule was measured on the day before and 1, 4, and 7 days after surgery. Oral bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Our data further reveal that the abundance of Fusobacterium in T-site at CRC stage III but not in other conditions is higher than those in oral cavity with CRC ( Figure 3 A). However, the absolute total number of bacteria in colon is higher than that in oral cavity (10 11 CFU/mL in colon vs 10 7 CFU/mL in oral cavity) [ 47 , 48 ]. Therefore, the absolute number of Fusobacterium in colon is higher than that in oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Our data further reveal that the abundance of Fusobacterium in T-site at CRC stage III but not in other conditions is higher than those in oral cavity with CRC ( Figure 3 A). However, the absolute total number of bacteria in colon is higher than that in oral cavity (10 11 CFU/mL in colon vs 10 7 CFU/mL in oral cavity) [ 47 , 48 ]. Therefore, the absolute number of Fusobacterium in colon is higher than that in oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…For these subjects, implementation of oral care intervention was impossible during the acute stage. The number of bacteria on the tongue surface is known to increase after 2 or 3 days following surgical operation [ 33 , 34 , 35 ]. The oral condition of patients at the acute stage may be similar to that of patients immediately after surgical operation.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies comparing multiple locales reported that the microorganisms count was highest on the tongue surface. Therefore, the number of microorganisms on the tongue surface could be representative of the majority of microorganisms within the entire oral cavity 39,40 . Fourth, we did not assess detailed systemic factors, including the variety and severity of stroke or ADL.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the number of microorganisms on the tongue surface could be representative of the majority of microorganisms within the entire oral cavity. 39,40 Fourth, we did not assess detailed systemic factors, including the variety and severity of stroke or ADL. Assessment of these factors could have allowed a more detailed evaluation of the relationship between systemic factors and the microorganism number on the tongue surface.…”
Section: F I G U R Ementioning
confidence: 99%